The Effect of Good Corporate Governance, Leverage, and Size Company Against Performance Finance - Dela Nila Rahayu; Khomeiny Yunior; Emia Leniatri Sembiring; Veri Alessandro Butar-Butar; Fauzi (International Journal Of Economics Social And Technology, 2023)
In the world of banking, there are each other dependency between application Good Corporate principles Governance, Leverage and Company Size, but not individually direct seen. Good Corporate Governance relates to the system that consists from structure and process. The better the implementation system manage company, then system GCG will give protection Which effective to company, Financial leverage is defined as use asset or liability to upgrade performance or profit something business or investment, meanwhile size company reflect total asset of company. Investigate governance influence good company, Leverage and Company Size against Performance Finance company food and drinks public in Indonesia. Type this research is approach quantitative. The sample used in this study was obtained based on that criteria has determined through purposive sampling on the company manufacturing in industry food and drink. From total sample 72 company, there is 31 observations balance sheets of 72 companies. which method used in this research is analysis multiple linear regression using the SPSS program version 22. The results of this study show that GCG variables have an effect positive to performance finance, meanwhile influential leverage variable negative to financial performance and size company influential negative to financial performance. Variable the influential positive to results performance finance.